Answer:
x = -14
Step-by-step explanation:
The expression to write in this problem is:
"the sum of x and 12 equals the sum of half of x and 5"
We have:
- The sum of x and 12 is: ![x+12](https://tex.z-dn.net/?f=x%2B12)
- The sum of half of x and 5 is: ![\frac{1}{2}x+5](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dx%2B5)
So, the equation to write in this problem is
![x+12=\frac{1}{2}x+5](https://tex.z-dn.net/?f=x%2B12%3D%5Cfrac%7B1%7D%7B2%7Dx%2B5)
We solve it as follows:
1) First, we subtract
from both sides, and we get
![x-\frac{1}{2}x+12=\frac{1}{2}x-\frac{1}{2}x+5\\\frac{1}{2}x+12=5](https://tex.z-dn.net/?f=x-%5Cfrac%7B1%7D%7B2%7Dx%2B12%3D%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B1%7D%7B2%7Dx%2B5%5C%5C%5Cfrac%7B1%7D%7B2%7Dx%2B12%3D5)
2) Then, we subtract 12 from both sides:
![\frac{1}{2}x+12-12=5-12\\\frac{1}{2}x=-7](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dx%2B12-12%3D5-12%5C%5C%5Cfrac%7B1%7D%7B2%7Dx%3D-7)
3) Now we multiply both sides by 2:
![\frac{1}{2}x\cdot 2=-7\cdot 2\\x=-14](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dx%5Ccdot%202%3D-7%5Ccdot%202%5C%5Cx%3D-14)
So, this is the solution.
Answer:
Option B is correct
Left 1 unit.
Explanation:
According to the graph theory of transformation:
y = f(x+k)=![\left \{ {{k>0 shift graph of y= f(x) left k unit} \atop {k](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bk%3E0%20shift%20graph%20of%20y%3D%20f%28x%29%20left%20k%20unit%7D%20%5Catop%20%7Bk%3C0%7D%20shift%20graph%20of%20y%3D%20f%28x%29%20right%20%7Ck%7C%20unit%7D%20%5Cright.)
Given the parent function:
and the function
we can write it as:
g(x)=
[ ∴
]
Therefore, vertex of the graph of the function
is 1 units to the left of the vertex of the graph of the function
.
Answer:
The fifth term is the middle term of nine, with coefficient given by all the ways of choosing 4 items out of 8
, namely the ways of choosing 4
a
's out of 8 binomial factors.
Step-by-step explanation:
7/11 in decimal form rounded to the nearest thousandth is : 0.636